2021
DOI: 10.3389/fphys.2021.716520
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis, Host Metabolism, and Non-communicable Diseases: Trialogue in the Inborn Errors of Metabolism

Abstract: Inborn errors of metabolism (IEMs) represent a complex system model, in need of a shift of approach exploring the main factors mediating the regulation of the system, internal or external and overcoming the traditional concept of biochemical and genetic defects. In this context, among the established factors influencing the metabolic flux, i.e., diet, lifestyle, antibiotics, xenobiotics, infectious agents, also the individual gut microbiota should be considered. A healthy gut microbiota contributes in maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 166 publications
(251 reference statements)
0
8
0
Order By: Relevance
“…No other biotics are added to the analysed PS for PKU infants. Given the known status of gut dysbiosis in PKU following Phe-restricted diet [ 43 ], the early modulation of the gut microbiota, also achievable through the addition of biotics (e.g., HMOs, GOS/FOS respecting 9:1 ratio) to infant protein substitutes, could be considered to have beneficial effects on dysbiosis and microbiota–gut–liver–brain axis, although results from clinical intervention studies are needed. A systematic review of the committee on Nutrition of the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) on supplementation of infant formula with probiotics and/or prebiotics highlighted the absence of safety concerns in relation to growth and development, but more experimental research is needed [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…No other biotics are added to the analysed PS for PKU infants. Given the known status of gut dysbiosis in PKU following Phe-restricted diet [ 43 ], the early modulation of the gut microbiota, also achievable through the addition of biotics (e.g., HMOs, GOS/FOS respecting 9:1 ratio) to infant protein substitutes, could be considered to have beneficial effects on dysbiosis and microbiota–gut–liver–brain axis, although results from clinical intervention studies are needed. A systematic review of the committee on Nutrition of the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) on supplementation of infant formula with probiotics and/or prebiotics highlighted the absence of safety concerns in relation to growth and development, but more experimental research is needed [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The management of these diseases usually consists of an exclusion dietary regimen that can reduce gut microbial biodiversity by promoting a state of dysbiosis [ 162 , 163 ]. Hence, IEMs represent a good model to evaluate how special diets are related to specific bacteria profiles that, in turn, could be associated with a characteristic clinical phenotype (“enterophenotype”) [ 164 ].…”
Section: Main Special Diets During Childhoodmentioning
confidence: 99%
“…Dysbiosis in the gut has been associated with obesity and metabolic syndromes in children in many clinical studies conducted worldwide 134–143 . While these alterations in GM composition could also be due in part to the altered diet or metabolic state of obese children, a longitudinal study in Norway demonstrated that GM composition at 2 years of age was predictive of BMI at age 12 144 .…”
Section: Obesity and Metabolic Disordersmentioning
confidence: 99%
“…133 Dysbiosis in the gut has been associated with obesity and metabolic syndromes in children in many clinical studies conducted worldwide. [134][135][136][137][138][139][140][141][142][143] While these alterations in GM composition could also be due in part to the altered diet or metabolic state of obese children, a longitudinal study in Norway demonstrated that GM composition at 2 years of age was predictive of BMI at age 12. 144 Furthermore, another study identified gut dysbiosis in prediabetic children, 17 suggesting that alterations in GM composition can also precede the onset of metabolic syndromes.…”
Section: Obesity and Metabolic Disordersmentioning
confidence: 99%